Specific removal of C-reactive protein by apheresis in a porcine cardiac infarction model - Slagman, Anna; Bock, Christopher; Abdel-Aty, Hassan; Vogt, Birgit; Gebauer, Frank; Janelt, Gunnar; Wohlgemuth, Franziska; Morgenstern, Rene; Yapici, Gülcan; Puppe, Astrid; Modersohn, Diethelm; Mans, Dörte; et al. (Blood purification, 2011)
BACKGROUND: C-reactive protein (CRP) is a possible causative factor of the destructive processes observed during the weeks after myocardial infarction. METHODS: We developed a clinically relevant animal model including the removal of CRP from blood plasma utilizing a specific CRP adsorber and the visualization of the infarct scar in the living animal by cardiovascular magnetic resonance imaging as a tool to investigate the impact of CRP after acute myocardial infarction. RESULTS: We describe the facets of this model system and kinetics of clinical blood parameters like CRP and troponin. In addition, we demonstrate the potency of CRP apheresis reducing CRP levels by ~70% in the established treatment system. CONCLUSION: We showed for the first time that it is possible to conduct apheresis at the following 2 days after acute myocardial infarction in a porcine infarction model and to analyze the infarct by cardiovascular magnetic resonance imaging at day 1 and 14.
Published online: December 7, 2010
Gesehen am 18.06.2021